Adherence therapy in hypertensive patients treated in Basic Health Units in a city of RS (Research, Society and Development, 2023)
Systemic Arterial Hypertension is a chronic non-communicable disease characterized by blood pressure levels above 140 and/or 90 mmHg. It may be increased by the presenceof others risk factors, sucha as obesity, diabetes mellitus and dyslipidemias, in addition to the incorrect use of antihypertensive drugs. The aim of this search is analyse the use of antihypertensive drugs by hypertensive patients treated in Health Unic System in Pinheiro Machado, a city of RS. A questionnaire was apllied in September 2021. Along with the questionnaire, the Morisky and Green test was performed. The prevalence of respondents was early people and female; the most commonly used class of drugs were angiotensin receptor blocker, beta-blocker and thiazide diuretics. The conclusion is that the respondents have a good drug treatment adherence, even though most of them are elderly, wich could interfere the follow-up of pharmacologic therapy. However, polypharmacy was not observed, wich may promove the therapy adherence, associated with other factors sucha as the purchase of medicines through the Popular Pharmacy Program or in the municipal public network and participation in a walking group.